Implementation of eco-enzyme technology: an innovative solution for organic waste management - Proni, Raffles Putra; Putri, Elysia Tanya; Fathmi, Nur Fajria Amalia; Yulianti, Devi; Septiani, Melti; Azhar, Fawwaz Nur; Baehaki, Ahmad; Maharani, Siti Destiana; Sudiani, Rizka Falah; Salsabila, Adinda Kanza; Rofikoh, Siti Nayatu; Lestari, Rini Dwi; Yulianti, Amalia Dwi; Faizah, Nabila; Manik, Heni Novyani; Nurlaila, Sinta; Oktaviani, Risma; Abdullah, Syarif (Faculty of Engineering, Universitas Sultan Ageng Tirtayasa, 2025)
Waste management remains a pressing challenge in modern society, largely due to limited public awareness regarding its importance. This study offers a transformative approach by redefining waste—particularly organic waste—not as mere refuse, but as a potential economic asset. Although biodegradable, organic waste is often left untreated, leading to missed opportunities for resource recovery. This research highlights the utilization of eco-enzyme, a product of organic waste fermentation over a three-month period, as an innovative and sustainable waste treatment method. The resulting eco-enzyme liquid functions effectively as a natural cleaning agent and soil enhancer, contributing to environmental restoration by reducing heavy metal content and stabilizing soil pH. From an economic standpoint, the use of eco-enzyme reduces dependence on conventional cleaning products, thereby lowering household expenses. Overall, the findings advocate for a paradigm shift in organic waste handling—demonstrating its dual value in environmental improvement and economic efficiency—while laying the groundwork for more sustainable waste management models. Pengelolaan limbah masih menjadi tantangan yang mendesak dalam masyarakat modern, terutama karena terbatasnya kesadaran masyarakat mengenai pentingnya limbah. Studi ini menawarkan pendekatan transformatif dengan mendefinisikan ulang limbah—khususnya limbah organik—bukan hanya sebagai sampah, tetapi sebagai aset ekonomi yang potensial. Meskipun dapat terurai secara hayati, limbah organik sering kali tidak diolah, sehingga menyebabkan hilangnya peluang untuk pemulihan sumber daya. Penelitian ini menyoroti pemanfaatan eko-enzim, produk fermentasi limbah organik selama periode tiga bulan, sebagai metode pengelolaan limbah yang inovatif dan berkelanjutan. Cairan eko-enzim yang dihasilkan berfungsi efektif sebagai agen pembersih alami dan penambah tanah, berkontribusi pada pemulihan lingkungan dengan mengurangi kandungan logam berat dan menstabilkan pH tanah. Dari sudut pandang ekonomi, penggunaan eko-enzim mengurangi ketergantungan pada produk pembersih konvensional, sehingga menurunkan pengeluaran rumah tangga. Secara keseluruhan, temuan tersebut menganjurkan perubahan paradigma dalam penanganan limbah organik—yang menunjukkan nilai gandanya dalam perbaikan lingkungan dan efisiensi ekonomi—sambil meletakkan dasar bagi model pengelolaan limbah yang lebih berkelanjutan.